Cultural Interactions Between the Societies of the ‘Old Europe’ and the Steppe ‘Kurgan People’ During the Last Quarter of the 4th Millennium BC: Case Study of Serezlievka Local Group - Ivanov, Mykyta; Tupciyenko, Mykola (Archaeologia Lituana, 2022)
Cultural interactions between the societies of Old Europe and the Steppe ‘Kurgan people’ played a significant role in the academic writings of Maria Gimbutas. In her texts, the interplay between mentioned human groups was described as a dichotomy and was put into a framework of violent struggle. Three waves of destructive intrusion of steppe pastorals were reconstructed and the determinative role of ‘kurgan people’ in the spread of Indo-European nations was described (Gimbutas, 1993). However, although Gimbutas’ model is still influential and is used as a methodological framework for the most recent genomic studies (Haak et al., 2015), (Allentoft et al., 2015), (Juras et al., 2018), (Scorrano et al., 2021), there are certain archaeological data that allow suggesting a more complicated interaction than simple ‘east-to-west’ migration. In the current paper, we will publish a rare example of a kurgan burial with mixed Late Trypillia and ‘steppe’ traits, excavated by one of the authors in 1989 near the village of Pomichna. The context of similar burials discovered in the south of Eastern Europe between the South Buh and Dnieper rivers will be provided. The emergence of the Serezlievka local group with a hybrid Trypillia-steppe identity at the end of the 4th millennium BC will be conceptualized.
Keywords: Late Trypillia; kurgan; pottery; steppe; jewelry; anthropomorphic figurines; Indo-Europeans